Developing the dimensions of tourism volunteering - Holmes, Kirsten; Smith, K.; Lockstone, L.; Baum, T. (Routledge, 2010)
Volunteers within tourism settings are of growing interest. Research to date has been fragmented either focusing on individuals volunteering in their community (i.e., hosts) or tourists volunteering at a destination (i.e., guests). In this paper, the tourism and leisure literature on volunteering is synthesized and the host and guest streams of volunteering critiqued according to four defining dimensions: setting, time commitment, level of obligation, and remuneration. These dimensions are refined using interview data to propose a model of tourism volunteering where host and guest volunteering are related rather than distinct. A simple host-guest dichotomy misses the shared and distinct complexities of tourism volunteering.